ELEKTROKOAGULASI YELLOW-CGN DENGAN MENGGUNAKAN BAHAN YANG MUDAH DIDAPATKAN: PENGARUH WAKTU - Novrian Dony; Firda Herlina (Universitas Lambung Mangkurat, 2016)
The aim of this research to find the effect of time in electrocoagulation of yellow gcn. Electrocoagulation process use material that eazy to find and simple. Electrode in this research use aluminium from the waste of aluminium board industry around Sasirangan Industri and use carbon from battery. Current in Electrocoagulation processes use handphone. Result shown that effective time is used in electrocoagulation is 4 hours and 4 hours to wait yellow gcn coagulate.